A Simplified and Practical Surgical Treatment for Medial Ectropion: A Case Report. Issue 5 (May 2019) - Pinelli, Massimo; Starnoni, Marta; De Santis, Giorgio
Abstract : Summary: We present the case of a 81-year-old patient with right facial palsy suffering from recurrent medial ectropion with lower lateral dislocation of the lacrimal punctum causing epiphora and photophobia. The patient was first treated for ectropion with lateral tarsal strip procedure. Unfortunately, this surgical procedure did not get the expected result. This was the reason we used the Mitek anchor system to fix the lower lateral dislocation of the punctum. We had no recurrence of symptoms during a follow-up period of 18 months.